Визуализация образования с использованием современных веб-технологий - Спыну, Екатерина (CEP USM, 2024)
The website 'RepetitorMD' showcases modern educational tools like HTML, CSS, PHP, and phpMyAdmin for dynamic, interactive learning experiences across various devices, emphasizing responsive design and user engagement.